Extracurricular educational programs and school readiness: Evidence from a quasi-experiment with preschool children - Anna Makles; Kerstin Schneider (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The paper adds to the literature on extracurricular early childhood education and child development by exploiting unique data on an educational project in Germany, the Junior University (JU). By utilizing a quasi-experimental study design we estimate the causal short-term effect of JU enrollment and show that attending JU significantly leads to higher school readiness, i.e. higher cognitive and non-cognitive abilities. Although the effect of attending JU on school readiness is quite small, the results are plausible and pass various robustness checks.
Keywords: I20; I21; I28; 330